Authentizität beim Lernen – Eine empirische Untersuchung zur Vermittlung des globalen Klimawandels im Geographieunterricht - Flake, Sabrina; Cermak, Jan; Sprenger, Sandra (Journal of Geography Education, 2015)
This study analyzes to what degree climatology and especially global climate change with its natural and human causes and mitigation measures are part of Geography classes in German schools. With a focus on authenticity, the extent to which authentic materials are used is examined. Authenticity is used in the sense of original, unaltered, genuine objects, and accordingly, authentic materials are those that have not been specifically designed or adapted for teaching. As a basis for empirical studies, an analysis of Geography text books is performed, based on qualitative content analysis, complemented by a teacher survey and a student survey. This article presents the central results of the study and draws out implications and suggestions for using authenticity in climatology-focused Geography lessons. In the books and schools considered, aspects of climate change are not included to an extent that would allow students to acquire professional competence in dealing with climate change. Authentic materials are not used in climate-focused Geography lessons in the schools considered.
Keywords: Geography education, climate change, authenticity, authentic materials, different perspectives